Journal of urban ecology (Oxford University Press, 2015)
Journal of Urban Ecology covers all aspects of urban environments. This includes the biology of the organisms that inhabit urban areas, human social issues encountered within urban landscapes, and the diversity of ecosystem services. The journal covers, but is not limited to, urban climate, urban sustainability, soils, vegetation, animals, ecosystems, green spaces, parks, people's use of the environment, planning, management and policy making. The journal covers the ecology in cities and the ecology of cities, in both developed and developing countries. These subjects include basic ecological questions in urban areas, such as how ecological patterns and processes differ in cities compared to other environments and what effect urbanisation has on the ecology of organisms, as well as topics on the interactions between ecological and social systems in the urban setting.